Educate or adjudicate? Socio-economic heterogeneity and welfare - Bilin Neyaptı (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
This paper presents a model to explore the welfare effects of the government's choice over two types of public goods provision: domestic regulatory and security spending (adjudication) versus education. Output is a function of physical and social capital, both of which can be heterogeneous across the regions. Local social capital is exposed to spillover effects of other regions. Education spending increases social capital, whereas adjudication spending increases total factor productivity. The solution in an OLG framework indicates that the welfare maximizing ratio of education spending is negatively related with the past levels of social capital stock and the degree of social cohesion, but positively related with the current levels of aggregate income and the tax rate. Simulations of the model's temporal solution reveal the short-run and long-run difference, reversing the positive effects of the tax rate and the income level, which is a crucial point. Income and cultural homogeneity are associated positively with the level of aggregate income and social cohesion whereas the relationship between income distribution and social cohesion is non-linear in the short-run.
Keywords: E02; E6; H11; H52; I24; I25; I31; Z18; 330; Economic Development; Income Equality; Public Spending; Social Capital; Social Cohesion